Evaluasi Dan Perancangan Ulang Antarmuka Pengguna Menggunakan Metode Usability Heuristic - Dicky Indrayan; Rosa Reska Riskiana; Aristyo Hadikusum (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Climatebase is a website that provides job vacancies all over the world. The large number of user interactions every day on the website makes the Climatebase website must provide good interaction and usability in terms of user interface to its users. Based on observations and interviews conducted with Climatebase, the results are that Climatebase provides evaluation recommendations on the job board feature based on evaluations from users and Climatebase. Based on the results of the initial usability evaluation on the Job Board feature on the Climatebase website, a severity ratings value of 1.13 was obtained with three problematic usability aspects, namely Consistency and Standard, Help Users Recognize, Diagnose and Recover from and Help and Documentation. The results of the usability evaluation on three aspects received Severity Ratings in the range 1.67 to 2, including minor repair problems in low priority, therefore the focus of this research is design improvement. Evaluation was carried out using the heuristic evaluation method and redesigning the user interface using the principles of Human Centered Design. The results of the redesign on the Climatebase website get a severity rating of 0.84 including the Cosmetic problem category, no need to fix it unless there is additional time.